Performance Enhancement for LTE-A Networks Using Small Nodes - Yahya, A.; Chuma, J.; Mosutlha, I.; Aldhaibani, Jaafar.A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Long Term Evolution- Advanced (LTE-A) is the succeeding version of LTE system to enhance capacity and coverage. Multi-hop relay is one of technologies supported by LTE-A, which aims to enhance the cell-edge capacity. Multi hop technologies are categorized into a fixed relay node (FRN) and a moving relay node (MRN). This paper proposes a system model, which improves the capacity and throughput by employing moving and fixed relay coupled with half-duplex mode. It was expected that the MRN installed on the top of vehicles improves the capacity and throughput for vehicular users when the vehicles move at high speed, while FRN deployed far from BS enhances the coverage at cell edge. Amplify and forward (AF) and decode and forward (DF) protocols were used with these two types of relays. Furthermore, the relay channel and amplification gain were derived in this paper to get the maximum advantage via multi-hop technology. Simulation and analytical results show an increase in the throughput from 1.8Mbps to 3.7Mbps for 35 users after employing the MRN on moving vehicle. Furthermore this value improved to 4.1Mbps after employing the MRN within a LTE-A cell coupled with FRNs deployed around BS, according to the proposed location.